PENGARUH METODE PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP PRESTASI BELAJAR MAHASISWA: SEBUAH EKSPERIMEN SEMU - Zulfikar Ismail; Lilik Purwanti (Universitas Brawijaya, 2011)
Abstract: The Effect of Cooperative Learning Method in Jigsaw Type on the Students’ Learning Performance: A Semi Quasi Experiment. This study is aimed to prove whether there are differences in students’ learning achievements in studying Financial Accounting I about IFRS between Jigsaw cooperative learning method and conventional learning method. The subject of this study is students of Accounting Department of Brawijaya University of Malang who were taking financial accounting I in the short course of 2009–2010. The data analysis is carried out by difference test to prove students’ learning achievement taught using Jigsaw cooperative learning method and conventional method. The study proves that in understanding financial accounting about IFRS, the learning process using Jigsaw cooperative learning method is better than the conventional method.Abstrak: Pengaruh Metode Pembelajaran Kooperatif Tipe Jigsaw terhadap Prestasi Belajar Mahasiswa: Sebuah Eksperimen Semu. Penelitian ini bertujuan untuk membuktikan perbedaan antara prestasi belajar mahasiswa dalam mempelajari Akuntansi Keuangan I tentang IFRS, antara tipe jigsaw dan metode konvensional. Penelitian ini menggunakan mahasiswa Departemen Akuntansi Univerrsitas Brawijaya Malang yang mengambil mata kuliah pendek tahun 2009-2010. Analisis data dilakukan dengan uji beda untuk membuktikan prestasi mahasiswa yang diajarkan dengan metode jigsaw dan metode konvensional. Studi membuktikan bahwa metode pembelajaran tipe jigsaw lebih baik daripada metode konvensional.